2018
DOI: 10.3168/jds.2017-13945
|View full text |Cite
|
Sign up to set email alerts
|

Rapid baso-apical translocation of Mycobacterium avium ssp. paratuberculosis in mammary epithelial cells in the presence of Escherichia coli

Abstract: Infection of mammary gland cells with bacterial pathogens begins with adhesion, invasion, and persistence within the cells or systemic distribution. Some bacteria, such as Escherichia coli, are known to causes bovine mastitis, resulting in acute proinflammatory responses in the mammary tissue. Mycobacterium avium ssp. paratuberculosis (MAP), the etiological agent of paratuberculosis, is able to spread to distant organs after crossing intestinal cells, reaching the mammary gland and potentially being released i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Coinfection study of MAP and E. coli isolated from bovine mastitis was recently described by Schwarz et al (2018). In this study, the previous E. coli infection of bovine mammary epithelial cell line (MAC-T) increased a rapid baso-apical translocation of MAP to the supernatant of the cells.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…Coinfection study of MAP and E. coli isolated from bovine mastitis was recently described by Schwarz et al (2018). In this study, the previous E. coli infection of bovine mammary epithelial cell line (MAC-T) increased a rapid baso-apical translocation of MAP to the supernatant of the cells.…”
Section: Introductionmentioning
confidence: 67%
“…paratuberculosis (MAP) even being released by milk, appear to poorly stimulate the local inflammatory response and is not considered as the etiologic agent of classic mastitis (Larsen and Miller 1978). Recently, a study showed that cows with E. coli mastitis potentially can attract MAP from distant sites and release it into milk more efficiently when compared with cows without mastitis (Schwarz et al 2018). However, the mechanisms of how a non-mastitic pathogen can infect the mammary gland and interfere in a subsequent infection by another mastitic pathogen are still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations